Mengungkapkan Makna Serta Emosi pada Lagu Nadin Amizah “Ah” - Nia Virdayanti (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
The aim of this research is to analyze the meaning and emotions contained in the song “Ah” by Nadin Amizah. The research method used is descriptive. The research results show that the song “Ah” contains a very deep meaning of happiness and love, which describes the experience of someone who finally finds the right partner after going through a long waiting process. The emotions contained in this song are happiness, luck, and relief, which depicts harmony in a loving relationship full of affection. This research can provide insight into how songs can be a means of expressing human emotions and experiences, as well as how analysis of song lyrics can be used to understand the meaning and emotions contained in a song.